2022
DOI: 10.1021/acs.jmedchem.2c00455
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase-Activatable Prodrugs Based on an Alkoxyamine Platform to Deliver Alkyl Radicals Cytotoxic to Tumor Cells

Abstract: Current chemotherapies suffer low specificity and sometimes drug resistance. Neutrophil elastase activity in cancer is associated with poor prognosis and metastasis settlement. More generally, tumors harbor various and persistent protease activities unseen in healthy tissues. In an attempt to be more specific, we designed prodrugs that are activatable by neutrophil elastase. Upon activation, these alkoxyamine-based drugs release cytotoxic alkyl radicals that act randomly to prevent drug resistance. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Neutrophil elastase exerts pro-tumorigenic effects ( 24 ) and promotes dissemination and metastasis of tumor cells ( 25 ). It is involved in awakening cancer cells that are in dormancy, which has been linked to cancer recurrence ( 12 ) and has shown association with prognosis of cancer patients ( 26 ). Cancer cells have the capacity to produce neutrophil elastase ( 27 ) and upregulation of neutrophil elastase has been observed in various types of cancer ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil elastase exerts pro-tumorigenic effects ( 24 ) and promotes dissemination and metastasis of tumor cells ( 25 ). It is involved in awakening cancer cells that are in dormancy, which has been linked to cancer recurrence ( 12 ) and has shown association with prognosis of cancer patients ( 26 ). Cancer cells have the capacity to produce neutrophil elastase ( 27 ) and upregulation of neutrophil elastase has been observed in various types of cancer ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in awakening cancer cells that are in dormancy, which has been linked to cancer recurrence ( 12 ) and has shown association with prognosis of cancer patients ( 26 ). Cancer cells have the capacity to produce neutrophil elastase ( 27 ) and upregulation of neutrophil elastase has been observed in various types of cancer ( 26 ). A high level of neutrophil elastase in breast tumor extracts is regarded as an independent indicator of poor prognosis and poor response to tamoxifen therapy ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the materials used, the preparation of the alkoxyamines and chiral AuNPs, and the measurement techniques is given in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…5 More recently, Seren S. et al reported a new series of alkoxyamines, based on phenol or aniline cores, that also inhibited U87-MG cell survival but with IC 50 values 25 times higher than ALK4 in the same cell model. 16 To further investigate ALK4, ALK5, ALK9 and ALK13 anticancer properties, a Transwell assay was carried out. It showed that the alkoxyamines were also effective in inhibiting GBM cell migration at low doses (Fig.…”
Section: Selection Of the Most Effective Alkoxyamines In Inhibiting P...mentioning
confidence: 99%